Risk factors for anastomotic leakage after rectal cancer resection and reconstruction with colorectostomy: a retrospective study with bootstrap analysis - Warschkow, René; Steffen, Thomas; Thierbach, Jutta; Bruckner, Thomas; Lange, Jochen; Tarantino, Ignazio (Annals of surgical oncology, 2011)
This study was designed to apply modern statistical methods to evaluate risk factors for anastomotic leakage after rectal cancer resection in a retrospective cohort of patients who received a colorectostomy. Whereas a diverting stoma and tumor height are considered proven risk factors for anastomotic leakage, a lack of evidence about additional risk factors persists.